Genetic diversity and interrelationship among clusterbean (Cyamopsis tetragonoloba) genotypes for qualitative traits - PATHAK, RAKESH; SINGH, MANJIT; HENRY, A (The Indian Journal of Agricultural Sciences, 2011)
A study was conducted during 2006–07 to assess the extent of genetic variability and qualitative characters of clusterbean (Cyamopsis tetragonoloba L. Taub.). The range, genotypic and phenotypic coefficient of variation, heritability, genetic advance and correlation among seven qualitative characters were estimated in 40 genotypes of clusterbean. The genotypes showed considerable amount of variability for all the traits. Irrespective of their place of collection the genotypes were grouped into seven different clusters. Cluster analysis revealed that genotypes ‘HGS 884’, ‘HGS 26– 01’ and ‘HGS 02-20’ will be useful for genetic resources. High magnitude of heritability and genetic advance for gum, fibre and protein contents suggested that the genotypic variation in the present material for these characters is due to high additive genetic effects. Carbohydrates were positively correlated with endosperm and gum contents. Endosperm exhibited significant positive association with gum content while the association of protein was negative with gum and endosperm contents.